Glutamate Receptors in Neuroinflammatory Demyelinating Disease (Mediators of Inflammation)
Multiple sclerosis (MS) is a chronic demyelinating disease of the human central nervous system (CNS). The condition predominantly affects young adults and is characterised by immunological and inflammatory changes in the periphery and CNS that contribute to neurovascular disruption, haemopoietic cell invasion of target tissues, and demyelination of nerve fibres which culminate in neurological deficits that relapse and remit or are progressive. The main features of MS can be reproduced in the inducible animal counterpart, experimental autoimmune encephalomyelitis (EAE). The search for new MS treatments invariably employs EAE to determine drug activity and provide a rationale for exploring clinical efficacy. The preclinical development of compounds for MS has generally followed a conventional, immunotherapeutic route. However, over the past decade, a group of compounds that suppress EAE but have no apparent immunomodulatory activity have emerged. These drugs interact with the N-methyl-D-aspartate (NMDA) and α -amino-3-hydroxy-5-isoxazolepropionic acid (AMPA)/kainate family of glutamate receptors reported to control neurovascular permeability, inflammatory mediator synthesis, and resident glial cell functions including CNS myelination. The review considers the importance of the glutamate receptors in EAE and MS pathogenesis. The use of receptor antagonists to control EAE is also discussed together with the possibility of therapeutic application in demyelinating disease.